Critical analysis of the protection of end consumers in Slovenian electricity market legislation - Tomažič, Luka Martin (Podjetje in delo, 2020)
In this article, an in-depth analysis of the legislative framework, aimed at the protection of end consumers in the Slovenian electricity market, will be performed. To perform the analysis, first both the adequacy of the structure of the Slovenian Energy Act (hereinafter EZ-1) will be critically evaluated and then the merits of individual solutions will be ascertained. The evaluation will follow the structure of EZ-1 and will be performed in three main areas, according to the subsections of the Part 2 Chapter 1 Section 3 of EZ-1, namely regarding the general provisions, regarding the emergency and urgent supply, and regarding other provisions aimed at the protection of household and small business consumers. Several tests of quality of legislation will be applied to ascertain the quality of analysed provisions. Slovenian legislative solutions will be compared with analogue Croatian and Slovakian solutions, where applicable, and several aspects of protective legislation will be criticised.
Keywords: consumer protection; electricity market; energy law; legislation; nomotechnics; nomotehnika; pravo energetike; Slovenia; trg z elektriko; varstvo odjemalcev; zakonodaja